Self-regulation failure as a moderator of the pops–work outcomes relationships. Issue 7 (20th October 2020) - Palmer, Joshua C.; Hochwarter, Wayne A.; Ma, Shuang (Sara); Ferris, Gerald R.; Kiewitz, Christian
Abstract : Purpose: Drawing upon cognitive control theory, we examine the effects of self-regulation failure (SRF) on the relationships between perceptions of organizational politics (POPs) and tension, exhaustion, satisfaction, work effort, perceived resource availability and performance/contribution. Design/methodology/approach: We test hypotheses across three unique studies (Study 1: 310 employees from various occupations; Study 2: 124 administrative/support employees; Study 3: 271 Chinese hotel managers) using hierarchical moderated regression analyses. Findings: Across studies, results suggest that POPs had a minimal impact on work attitudes, behaviors and health-related outcomes when SRF was low. However, employees experiencing high SRF reported adverse consequences in high POPS settings. Research limitations/implications: These studies relied on self-report data. However, we implemented design features to mitigate potential concerns and analytic techniques to determine method effects. This paper contributed to the POPs literature by explaining how SRF and POPs interact to impact meaningful work outcomes. Practical implications: Leaders should receive training to help them identify and address indicators of SRF. Leaders can also implement intervention programs to help calm employees who experience SRF. Social implications: Leaders should receive training to help them identify and address indicators of SRF. Leaders can also implement programs to help assist employees who demonstrate adverse effects from SRF. Originality/value: This paper integrates the research on SRF and politics to examine the collective impact these variables have on workers. Our three-study package also addresses the call for more studies to examine how politics operate across cultures.